MANAJEMEN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI DALAM MENINGKATKAN MUTU PENDIDIKAN: STUDI KASUS DI SDIT AL-AMANAH BANDUNG - apri parantono; Tri Puspandari; Bambang Aviantono (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The quality of primary education is influenced by the effectiveness of human resource management; however, empirical evidence regarding the contribution of competency-based Human Resource Management (HRM) to educational quality improvement in private schools remains limited. This study aims to analyze the implementation of competency-based HRM and its impact on educational quality at SDIT Al-Amanah Bandung. The research employed a mixed-methods approach using a sequential explanatory design. Quantitative data were collected through a survey involving 45 educators and an analysis of school quality documents, while qualitative data were obtained through interviews and observations. Data were analyzed using descriptive statistics and thematic analysis. The findings indicate that the implementation of competency-based HRM contributed to improvements in educational quality, as reflected in enhanced school accreditation, student academic achievement, and the satisfaction levels of teachers and parents. Qualitative findings reveal that human resource planning, competency development programs, and performance-based reward systems fostered a professional work culture and strengthened organizational effectiveness. This study confirms that competency-based HRM is a strategic approach to improving educational quality through strengthening teacher competencies and sustaining institutional performance. The findings also offer a quality-oriented HRM model that may serve as a reference for private schools with similar characteristics. ABSTRAK Mutu pendidikan dasar dipengaruhi oleh efektivitas pengelolaan sumber daya manusia, namun bukti empiris mengenai kontribusi Manajemen Sumber Daya Manusia (MSDM) berbasis kompetensi terhadap peningkatan mutu pendidikan di sekolah swasta masih terbatas. Penelitian ini bertujuan menganalisis implementasi MSDM berbasis kompetensi dan pengaruhnya terhadap mutu pendidikan di SDIT Al-Amanah Bandung. Penelitian menggunakan pendekatan mixed-methods dengan desain sequential explanatory. Data kuantitatif diperoleh melalui survei terhadap 45 tenaga pendidik dan analisis dokumen mutu sekolah, sedangkan data kualitatif dikumpulkan melalui wawancara dan observasi. Analisis data dilakukan menggunakan statistik deskriptif dan analisis tematik. Hasil penelitian menunjukkan bahwa implementasi MSDM berbasis kompetensi berkontribusi terhadap peningkatan mutu pendidikan yang tercermin pada peningkatan akreditasi sekolah, capaian akademik siswa, serta kepuasan guru dan orang tua. Temuan kualitatif menunjukkan bahwa perencanaan SDM, pengembangan kompetensi, dan sistem penghargaan berbasis kinerja mendorong budaya kerja profesional dan efektivitas organisasi sekolah. Penelitian ini menegaskan bahwa MSDM berbasis kompetensi merupakan strategi penting dalam meningkatkan mutu pendidikan melalui penguatan kompetensi guru dan keberlanjutan kinerja institusi, serta dapat menjadi rujukan bagi sekolah swasta dengan karakteristik serupa.